2012
DOI: 10.1002/jssc.201200282
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ligand density and pore size on the adsorption of bovine IgG with DEAE ion‐exchange resins

Abstract: Immunoglobulin G is an important plasma protein with many applications in therapeutics and diagnostics, which can be purified effectively by ion exchange chromatography. The ligand densities and pore properties of ion-exchange resins have significant effects on the separation behaviors of protein, however, the understandings are quite limited. In this work, with bovine immunoglobulin as the model IgG, the adsorption isotherms and adsorption kinetics were investigated systematically with series of diethylaminoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…), column parameters (length, diameter, etc.) and operating variables (flow rate, gradient slope, sample loading, etc) …”
Section: Introductionmentioning
confidence: 99%
“…), column parameters (length, diameter, etc.) and operating variables (flow rate, gradient slope, sample loading, etc) …”
Section: Introductionmentioning
confidence: 99%
“…Adsorption kinetics of hIgG on G‐ABI resins with different ligand densities were measured by a batch method, as previously published . Two grams drained HCIC resins were added into 40 mL protein solution (1 mg/mL hIgG in 20 mM sodium phosphate buffer, pH 7.0) in a 50 mL flask.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of protein in the suspension was monitored on line by an UV monitor (UV Detector K‐2600, Knauer, Germany). The adsorption kinetics curves were fitted by the pore diffusion model using Matlab 7.5.0 (Mathworks, USA) as had been done in previous studies .The effective pore diffusivity ( D e ) was obtained for G‐ABI resins with different ligand densities.…”
Section: Methodsmentioning
confidence: 99%
“…In another publication, the adsorption capacities of the resin were found to increase with an increase in ligand density and a decrease in pore size, and an integrative parameter was proposed to describe the combined effects of ligand density and pore size. [19] It was also found that the effective pore diffusion coefficient of the adsorption kinetics was influenced by pore sizes of resins, but was relatively independent on the ligand densities of the resins.…”
Section: Introductionmentioning
confidence: 97%